Prevalence of Nonalcoholic Steatohepatitis‐Associated Cirrhosis in the United States: An Analysis of National Health and Nutrition Examination Survey Data. (April 2017) - Kabbany, Mohammad Nasser; Selvakumar, Praveen Kumar Conjeevaram; Watt, Kymberly; Lopez, Rocio; Akras, Zade; Zein, Nizar; Carey, William; Alkhouri, Naim
Abstract : Objectives: Nonalcoholic fatty liver disease (NAFLD) includes a wide spectrum of manifestations ranging from nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis (NASH), fibrosis and eventually cirrhosis. The prevalence of NAFLD has been shown to be increasing over time; however, the prevalence of NASH cirrhosis and advanced fibrosis over time has not been well studied. Estimate the changes in prevalence of NASH cirrhosis and NAFLD‐associated advanced fibrosis among adults in the United States. Methods: National Health and Nutrition Examination Survey (NHANES) data obtained during the periods from 1999–2002 and 2009–2012 were analyzed to estimate the prevalence of NASH cirrhosis and NAFLD‐associated advanced fibrosis in subjects aged ≥18 years at the time of enrollment. We excluded patients with viral hepatitis, excessive alcohol consumption, aspartate aminotransferase (AST) or alanine aminotransferase (ALT) >500 and patients who were pregnant. Cirrhosis was defined by AST to platelet ratio index (APRI) >2 and abnormal liver function tests. NASH cirrhosis was defined as cirrhosis that presented with at least one of the following: obesity, diabetes, insulin resistance (HOMA‐IR≥3), and metabolic syndrome. Advanced fibrosis was defined by using well‐established cutoff values for APRI, fibrosis‐4 index (FIB‐4) and NAFLD fibrosis score (NFS). Population weighted prevalence was calculated separately for two groups to account for complex sampling method of NHANES. Results: A total of 7034 NHANES participants from 1999–2002 and 2009–2012 group were included with mean age of 46.2±0.59 and 47.3±0.51 years, respectively, at the time of screening. The prevalence of NASH cirrhosis was significantly higher in 2009–2012 group (0.178% with an estimated 417, 524 American adults with NASH‐associated cirrhosis) compared to 1999–2002 group (0.072%); P value<0.05. The prevalence of NAFLD with advanced fibrosis also increased from 0.84 to 1.75% during the same time period ( P value<0.001) corresponding to 4, 104, 871 American adults. During these time periods, there were also significant increases in obesity (29.8 vs. 36.6%), diabetes (8.3 vs. 11.9%), and insulin resistance (34.7 vs. 42.1%); P value <0.005 for all of them. Conclusions: There has been a 2.5‐fold and 2‐fold increases in the prevalence of NASH cirrhosis and NAFLD‐associated advanced fibrosis, respectively, in 2009–2012 compared to 1999–2002. Extrapolation of NHANES data suggests that in 2010, 417, 524 in the US had NASH cirrhosis, and 4, 104, 871 had NAFLD‐associated advanced fibrosis. This represents a major disease burden and suggests the need for widespread programs to identify and treat those affected, and public health efforts aimed at controlling the burden of NAFLD and its complications.